Addition reaction curable organopolysiloxane composition
The organopolysiloxane composition addresses insufficient curing and platinum migration by using specific group ratios and a compatibility agent, ensuring effective film formation with reduced platinum content.
Patent Information
- Application Number
- JP2023512967
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-09
- Filing Date
- 2022-03-29
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2042-03-29
AI Technical Summary
Existing organopolysiloxane compositions using platinum catalysts for film formation face issues with insufficient curing at low platinum concentrations, leading to increased peeling force, residual adhesive, and migration of platinum to the adhesive surface, which is costly and can be catalytically poisoned by certain compounds.
A composition with organopolysiloxanes containing specific ratios of alkenyl and hydrogen groups, acrylic groups, and a direct chain olefin compatibility agent, using a small amount of platinum catalyst, to ensure complete curing and stable film formation.
The composition achieves full hardening with reduced platinum usage, maintaining peeling force and preventing platinum migration, thus lowering costs and reducing catalyst poisoning effects.
Smart Images

Figure 0007626204000001 
Figure 0007626204000002 
Figure 0007626204000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an addition reaction curable organopolysiloxane composition that can be cured with a small amount of a platinum group metal catalyst. [Background technology]
[0002] Conventionally, in order to prevent adhesion or fixation between sheet-like substrates such as paper or plastic and adhesive materials, a cured coating of an organopolysiloxane composition is formed on the substrate surface to impart release properties. As a method for forming a cured coating of organopolysiloxane on the substrate surface, the methods described in the following Patent Documents 1 to 3 are known. (1) A method of forming a release coating by addition reaction of an alkenyl-containing organopolysiloxane with an organohydrogenpolysiloxane using a platinum group metal compound as a catalyst (Patent Document 1: JP-A-47-32072). (2) A method of forming a peelable coating by condensation reaction of organopolysiloxane having functional groups such as hydroxyl groups and alkoxy groups using an organic metal salt as a catalyst (Patent Document 2: Japanese Patent Publication No. 1960-13709). (3) A method of forming a peelable coating by radically polymerizing an organopolysiloxane containing an acrylic group with a photoreaction initiator using ultraviolet light or electron beams (Patent Document 3: Japanese Patent Laid-Open Publication No. 162787 / 1979).
[0003] Among the above methods (1), (2), and (3), the method (1) for forming a peelable coating by addition reaction using a platinum catalyst is widely used because it has excellent curing properties and can meet the various release characteristic requirements from low to high speed peeling.
[0004] Conventionally, platinum group metal catalysts are often used in organopolysiloxane compositions for release paper or release film at a platinum group metal concentration of 60 to 400 ppm by mass. This is because, when the platinum concentration is less than 60 ppm by mass, the curing reaction does not proceed sufficiently, the cured film becomes soft, and the amount of remaining Si-H groups is large, resulting in high peel strength, and the presence of unreacted raw material organopolysiloxane, which becomes a migratory component, causes the organopolysiloxane to migrate to the adhesive surface to be bonded to the release paper, resulting in a decrease in adhesive strength.
[0005] Furthermore, platinum catalysts are expensive because they are rare precious metals, and therefore account for a large proportion of the cost of producing release paper or release film. Therefore, reducing the amount of platinum group metal catalysts leads to lower prices. In addition, some substrates contain components that act as catalyst poisons for platinum group metal catalysts, such as nitrogen compounds, sulfur compounds, and phosphorus compounds, and there has been a problem in that the poisonous components combine with the platinum group metals to prevent hardening by the addition reaction from proceeding.
[0006] As a method for curing with a small amount of platinum group metal catalyst, for example, Patent Documents 4 and 5 disclose the following compositions. (4) A polyorganosiloxane having at least two alkenyl groups bonded to silicon atoms per molecule, a hydrogenated organosiloxane having SiH groups at the terminals and side chains, and MD Vi A silicone composition comprising a Q resin and a hydrosilylation inhibitor, 1 / 2 and D Vi is RPSiO 2 / 2 and Q is SiO 4 / 2 R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and no aliphatic unsaturated bonds, and P is -(CH2) n It is an alkenyl group represented by -CH=CH2 (n is an integer of 0 to 6) (Patent Document 4: Japanese Patent No. 4221300). (5) A release coating composition comprising an alkenyl-functionalized polysiloxane, a silicon hydride-functionalized polysiloxane, and a platinum group metal, the alkenyl-functionalized polysiloxane being produced using a phosphazene base catalyst (Patent Document 5: JP-T-2009-513740).
[0007] However, the compositions described in Patent Documents 4 and 5 above are insufficient in curing as described below. For example, the composition described in Patent Document 4 contains highly reactive terminal Si-H groups and a film-forming MD Vi It is characterized by the use of Q resin, and in the examples, the composition is cured by heating at 150°C for 1.8 seconds at a platinum concentration of 60 ppm, but there is no description of a method for curing with a platinum amount less than 60 ppm. In addition, the extractables (amount of unreacted siloxane) in the cured film cured at a platinum concentration of 60 ppm are high at 5.8 to 6.5%, and there is a lot of uncured siloxane, so curing is insufficient. In addition, Patent Document 4 does not describe the release properties.
[0008] The composition described in Patent Document 5 is characterized in that the alkenyl-functionalized polysiloxane is a branched siloxane having MDQ units. It is described that the probability of forming a crosslinked film is increased by branched chains having terminal vinyl groups. In the examples described in Patent Document 5, tetradimethylvinylsiloxysilane is reacted with a phosphazene catalyst to synthesize an alkenyl-group-containing branched siloxane, and then a silicon hydride-functionalized polysiloxane and a platinum catalyst are mixed in an amount that results in a platinum concentration of 40 ppm, and the composition is cured under conditions of 100°C for 15 seconds and 115°C for 20 seconds. Patent Document 5 evaluates the cured state of the composition by extracting the cured product with methyl isobutyl ketone. The ratio of unreacted siloxane extracted is high in both cases, ranging from 6.4 to 25.2%, and curing is insufficient. In addition, other evaluations such as peeling properties are not performed.
[0009] In a fully cured film, the amount of unreacted siloxane extracted is generally at least 5% or less, preferably 3% or less. As described in Patent Documents 4 and 5, if the cured film contains 5% or more of unreacted siloxane, the siloxane migrates to the surface of the adhesive in contact with the release film, and the residual adhesion rate is significantly reduced. In addition, since many residual Si-H groups remain, the peel strength is higher than when the film is fully cured.
[0010] As a result of further investigations, the inventors have found that when an addition reaction type release paper silicone composition is blended with an organopolysiloxane compound having three or more (meth)acrylic groups per molecule and a weight average molecular weight of 1,000 or more, an addition reaction is possible with a small amount of platinum group metal catalyst, and a cured film with the same release strength as conventional products can be formed (Patent Document 6). [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 47-32072 [Patent Document 2] Special Publication No. 35-13709 [Patent Document 3] Japanese Patent Publication No. 54-162787 [Patent Document 4] Patent No. 4221300 [Patent Document 5] Special Publication No. 2009-513740 [Patent Document 6] International Publication No. WO2020 / 004254 Summary of the Invention [Problem to be solved by the invention]
[0012] The composition of Patent Document 6 certainly has excellent curing properties even at low platinum amounts of 15 ppm or 20 ppm, and has little uncured silicone. However, the acrylic group-containing organopolysiloxane has poor compatibility with other siloxanes (alkenyl group-containing organopolysiloxanes and organohydrogenpolysiloxanes), and although the composition is cloudy when mixed, the acrylic group-containing organopolysiloxane settles over time and separates after 10 to 60 minutes of standing; unless the lower layer is thoroughly mixed, curing will be insufficient with the small amount of platinum group metal catalyst.
[0013] In addition, it was found that the formulation of Patent Document 6, which uses a small amount of platinum group metal catalyst, is strongly affected by metal salts such as sodium salts and potassium salts, and the addition reaction does not proceed when the amount of metal salt in the composition is large.
[0014] The present invention has been made in view of the above circumstances, and has as its object the provision of an addition reaction curable organopolysiloxane composition which cures sufficiently even with a small amount of platinum group metal catalyst, exhibits good adhesion, and is capable of forming a cured coating having the same release strength as conventional coatings, and which, because the acrylic group-containing silicone does not settle out or separate over time, is capable of stably forming a release coating for silicone rubber or release paper or release film with a small amount of platinum group metal catalyst. [Means for solving the problem]
[0015] The present inventors have investigated various compatibilizing components to prevent separation, but in most cases, once compatibilization is achieved, the curing reaction does not proceed under a small amount of platinum group metal catalyst. However, they have found that by blending a linear olefin with a melting point of 20°C or less and a flash point of 40°C or more, it is possible to achieve both compatibilization and a curing reaction under a small amount of platinum group metal catalyst. Furthermore, they have found that it is effective to suppress the amount of metals other than platinum group metals in the composition to 100 ppm or less, since the curing reaction does not proceed under a small amount of platinum group metal catalyst if the amount of metal salt in the composition is large, and have come to the present invention.
[0016] Accordingly, the present invention provides the following addition reaction curable organopolysiloxane composition (hereinafter sometimes simply referred to as the organopolysiloxane composition or the composition). 1. An addition reaction curable organopolysiloxane composition comprising the following components (A) to (E), in which the amount of metals other than platinum group metals in the composition is 100 ppm or less: (A) an organopolysiloxane having an average of two or more silicon-bonded alkenyl groups per molecule: 100 parts by mass, (B) an organohydrogenpolysiloxane having an average of two or more silicon-bonded hydrogen atoms (Si-H groups) per molecule: an amount in which the number of moles of Si-H groups corresponds to 1 to 5 times the number of moles of alkenyl groups in component (A); (C) an organopolysiloxane having an average of one or more (meth)acrylic groups per molecule (excluding the above component (A)): 0.01 to 10 parts by mass, (D) a linear olefin having a melting point of 20° C. or lower and a flash point of 40° C. or higher: 0.1 to 20 parts by mass, (E) Platinum group metal catalyst: 1 to 50 ppm by mass of platinum group metal based on the total of components (A), (B), (C) and (D). 2. The addition reaction curable organopolysiloxane composition according to 1, further comprising 0.01 to 5 parts by mass of an addition reaction inhibitor (F) per 100 parts by mass of component (A). 3. The addition reaction curable organopolysiloxane composition of 1 or 2, wherein the weight average molecular weight of component (C) is 516 to 100,000. 4. The addition reaction curable organopolysiloxane composition according to any one of 1 to 3, wherein component (C) is an organopolysiloxane having a (meth)acrylic group in the side chain of the organopolysiloxane. 5. The addition reaction curable organopolysiloxane composition according to any one of 1 to 4, wherein component (C) is a cyclic siloxane having a (meth)acrylic group. 6. The addition reaction curable organopolysiloxane composition according to any one of 1 to 5, wherein component (C) is an organopolysiloxane having three or more (meth)acrylic groups in one molecule. 7. The addition reaction curable organopolysiloxane composition according to any one of 1 to 6, wherein component (D) is a linear olefin having a vinyl value (the number of moles of unsaturated functional groups contained in 100 g) of 0.30 to 0.58 mol / 100 g, a melting point of 20°C or lower, a flash point of 70°C or higher, and one or more unsaturated functional groups at the molecular terminals. 8. The addition reaction curable organopolysiloxane composition according to any one of 1 to 7, which is for use in a release paper or release film. Effect of the Invention
[0017] The organopolysiloxane composition of the present invention cures sufficiently despite the small amount of platinum group metal catalyst, and can form a cured coating having the same release strength as conventional addition reaction curing organopolysiloxane compositions. The small amount of platinum group metal catalyst allows for a significant reduction in production costs. In addition, curing by addition reaction is possible even on substrates containing catalyst poisons. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in detail below. [Component (A)] The component (A) of the present invention is an organopolysiloxane having an average of two or more silicon-bonded alkenyl groups per molecule, and may be used alone or in appropriate combination of two or more. Component (A) may be an organopolysiloxane having a structure represented by the following average composition formula (1). M a M Vi b D c D Vi d T e T Vi f Q g (1) (Wherein, M is RSiO 1 / 2 , M Vi is R2PSiO 1 / 2 , D is RSiO 2 / 2 , D Vi is RPSiO 2 / 2 , T is RSiO3 / 2 , T Vi is PSiO 3 / 2 , Q is SiO 4 / 2 Each R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and no aliphatic unsaturated bond. P is -(CH2) h -CH=CH2 (h is an integer of 0 to 6), a, b, d, and f each independently represent 0 or a positive number, b, d, and f are not all 0 at the same time, 2≦b+d+f≦500, c represents a positive number of 10 to 2,700, e represents a positive number of 0 or 200 or less, and g represents a positive number of 0 or 100 or less.
[0019] In the above formula (1), R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and no aliphatic unsaturated bond, preferably having 1 to 10 carbon atoms, more preferably having 1 to 8 carbon atoms. Specific examples include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, and dodecyl; cycloalkyl groups such as cyclohexyl; aryl groups such as phenyl, naphthyl, and tolyl; aralkyl groups such as benzyl and phenethyl; and groups in which a portion of the hydrogen atoms bonded to the carbon atoms of these groups have been substituted with halogen atoms, epoxy groups, amino groups, polyether groups, cyano groups, and hydroxyl groups. Among these, in order to reduce the curability and peel strength of the resulting cured product, it is preferable that 80 mol % or more of the total number of R is a methyl group.
[0020] P is -(CH2) h It is an alkenyl group represented by -CH=CH2 (h is an integer of 0 to 6), and specific examples thereof include a vinyl group, an allyl group, a butenyl group, a propenyl group, a 5-hexenyl group, an octenyl group, and a decenyl group, and among these, a vinyl group is preferable.
[0021] a, b, d, and f are each independently 0 or a positive number, b, d, and f are not 0 at the same time, and 2≦b+d+f≦500, preferably 2≦b+d+f≦200. a is preferably 0 or a positive number of 100 or less, b is preferably 0 or a positive number of 100 or less, d is preferably 0 or a positive number of 500 or less, and f is preferably 0 or a positive number of 100 or less.
[0022] c is 10 to 2,700, preferably 10 to 2,000, and more preferably 50 to 1,500. When c is less than 10, the amount of mist generated increases at a coating speed of 200 m / min or more, and the coated surface of the organopolysiloxane composition may become rough. On the other hand, when c exceeds 27,000, the kinetic viscosity of the organopolysiloxane composition becomes too high, and the coatability decreases, resulting in poor smoothness and a large difference in the coating amount depending on the part of the coated surface.
[0023] e is a positive number of 0 or less than 200, preferably a positive number of 0 or less than 20, and more preferably a positive number of 0 or less than 10. g is a positive number of 0 or less than 1,000, preferably a positive number of 0 or less than 10, and more preferably a positive number of 0 or less than 5.
[0024] The vinyl value of component (A) is preferably 0.001 to 0.7 mol / 100 g, more preferably 0.005 to 0.5 mol / 100 g, and even more preferably 0.01 to 0.1 mol / 100 g. If the vinyl value is less than 0.001 mol / 100 g, there may be too few reaction sites, leading to poor curing, whereas if the vinyl value exceeds 0.7 mol / 100 g, there may be too high a crosslink density, leading to an increase in the low-speed peel strength.
[0025] The weight average molecular weight of the (A) component is preferably 800 to 200,000, more preferably 800 to 150,000, and even more preferably 1,500 to 100,000. If the weight average molecular weight of the (A) component is lower than 800, the wettability increases and the component spreads easily, but the amount of coating on the substrate may be insufficient. If the weight average molecular weight exceeds 200,000, the component may not spread easily and the amount of coating on the substrate may vary. In the present invention, the weight average molecular weight of the (A) component is a value measured by gel permeation chromatography (GPC) analysis (solvent: toluene) based on the weight average molecular weight converted into polystyrene.
[0026] The viscosity of component (A) at 25°C is 7mm 2 / s or more 3 million mm 2 / s or less is preferable, and 10 mm 2 / s or more 10,000mm 2 / s or less is preferable, and 20 mm 2 / s or more 5,000mm 2 / s or less is more preferable. 2 If the viscosity is less than 1 / s, the kinetic viscosity of the entire composition will be low, and the coating amount may be insufficient. The kinetic viscosity is calculated from the absolute viscosity measured by the EMS method and the specific gravity. For example, an EMS viscometer (EMS-1000S, manufactured by Kyoto Electronics Industries Co., Ltd.) can be used as the measuring device.
[0027] Specific examples of such component (A) include polysiloxanes containing alkenyl groups at both ends, polysiloxanes containing alkenyl groups in the side chain, polysiloxanes containing alkenyl groups at one end and in the side chain, polysiloxanes containing alkenyl groups at both ends and in the side chain, and branched polysiloxanes containing alkenyl groups at the ends. The structural formula is M Vi 2D c , M2D c D Vi d , M Vi 3D c T1, M Vi 4D c T2, M Vi 2D c D Vid , M Vi 2D c Q1, M a D c D Vi d T Vi f (M, M vi , D, D Vi , T, T vi , Q, a, c, d, and f are the same as above. The same applies below.) etc. can be mentioned as further specific structural examples. Vi 2D 155 , M Vi 2D 100 , M2D 97 D Vi 3. M2D 26 D Vi 4. M2D 96 D Vi 4. M2D 95 D Vi 5. M Vi 3D 100 T1, M Vi 4D 100 T2, M Vi 2D 97 D Vi 1. M Vi 2D 95 D Vi 3. M3D 93 D Vi 3T Vi 1. M Vi 2D 2,000 , M2D 1,000 D Vi 20 etc. can be mentioned.
[0028] [(B) Component] The (B) component is an organohydrogenpolysiloxane having an average of two or more silicon-bonded hydrogen atoms (Si-H groups) per molecule, and may be used alone or in appropriate combination of two or more. The number of silicon-bonded hydrogen atoms (Si-H groups) per molecule is preferably 3 to 100, and more preferably 10 to 100. An organopolysiloxane crosslinked product is formed by addition reaction of the Si-H groups of this organohydrogenpolysiloxane with the alkenyl groups of the (A) component. The Si-H group content is preferably 0.001 to 3.5 mol / 100g, more preferably 0.01 to 2.5 mol / 100g, and even more preferably 0.02 to 2.0 mol / 100g. If the Si-H group content is too low, the curing property and adhesion may be deteriorated, and if it is too high, the peeling force may be heavy.
[0029] The organohydrogensiloxane of the component (B) is preferably one having a structure represented by the following formula (2). M i M H j D k D H L T m T H n Q o (2) (Wherein, M is RSiO 1 / 2 , M H is R2HSiO 1 / 2 , D is RSiO 2 / 2 , D H RHSiO 2 / 2 , T is RSiO 3 / 2 , T H HSiO 3 / 2 , Q is SiO 4 / 2 wherein R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and no aliphatic unsaturated bonds; i, j, k, and m are independently 0 or a positive number; L is 0 or a positive number of 100 or less; n is 0 or a positive number of 10 or less; o is 0 or a positive number of 10 or less; j, L, and n are not all 0 at the same time; and 2≦j+L+n≦100.
[0030] In the above formula (2), examples of R include those similar to those in the above formula (1), and among these, an alkyl group having 1 to 8 carbon atoms is preferred. In formula (2), i, j, k, and m are each independently 0 or a positive number, i is preferably 0 or a positive number of 10 or less, j is preferably 0 or a positive number of 10 or less, k is preferably 0 or a positive number of 100 or less, and m is preferably 0 or a positive number of 10 or less. L is a positive number of 0 or 100 or less, preferably 2 to 100, and more preferably 10 to 80. n is a positive number of 0 or 10 or less, preferably 0 or a positive number of 5 or less, and m is a positive number of 0 or 10 or less, preferably 0 or a positive number of 5 or less. j, L, and n are not 0 at the same time, and j+L+n is 2 to 100, and preferably a positive number of 10 to 80. o is a positive number of 0 or 10 or less, and preferably a positive number of 0 or 5 or less.
[0031] Specific examples of the organohydrogenpolysiloxane of component (B) include polysiloxanes containing hydrogensilyl groups at both ends, polysiloxanes containing hydrogensilyl groups in the side chain, polysiloxanes containing hydrogensilyl groups at one end and in the side chain, and polysiloxanes containing hydrogensilyl groups at both ends and in the side chain. The structural formula is M H 2D k , M2D H L , M2D k D H L , M H 2D k D H L , M H 3D k T1, M H 4D k T2, M i D k D H L T H n (M, M H , D, D H , T, T H, i, k, L, and n are the same as above. The same applies below.) etc. can be mentioned as further specific structural examples. H 2D 10 , M H 2D 100 , M2D 27 D H 3. M2D 97 D H 3. M2D 26 D H 4. M2D 25 D H 5. M2D 24 D H 6. M2D 96 D H 4. M2D 95 D H 5. M H 3D 100 T1, M H 4D 100 T2, M H 2D 97 D H 1. M2D 30 D H 5Q1, M H 2D 95 D H 3. M3D 93 D H 3T H The first prize can be mentioned.
[0032] The weight average molecular weight of component (B) is preferably 194 to 10,000, more preferably 874 to 5,000. If the weight average molecular weight of component (B) is too small, the adhesion may be significantly deteriorated, and if it is too large, the reactivity may be poor, the curing property may be reduced, and the residual adhesion rate may be reduced and the peeling force may be increased due to insufficient curing. In the present invention, the weight average molecular weight of component (B) is the weight average molecular weight calculated in terms of polystyrene by gel permeation chromatography (GPC) analysis (solvent: toluene).
[0033] The kinetic viscosity of component (B) at 25°C is 2 to 500 mm 2 / s is preferable, and 2 to 300 mm 2 / s is more preferable, and 5 to 200 mm 2 / s is more preferable. 2 If the molecular weight is less than 500 mm / s, the reactivity is good due to the small molecular weight, but the adhesion to the substrate may deteriorate. 2 If it exceeds 1 / s, the reactivity will deteriorate and the curing property will decrease, and there is a risk of a decrease in the residual adhesion rate and an increase in the peel force due to insufficient curing. The kinetic viscosity is calculated from the specific gravity by measuring the absolute viscosity using the same EMS method as above.
[0034] The amount of component (B) is 1 to 5 times, and preferably 1.2 to 3 times, the number of moles of Si-H groups relative to the number of moles of alkenyl groups in component (A). The amount of 1 to 5 times corresponds to 0.016 to 3.5 mol / 100 g in terms of the amount of Si-H functional groups. If the amount of component (B) is too small, the curing property and adhesion may be insufficient, while if the amount of component (B) is too large, the amount of remaining Si-H groups increases, resulting in a high peeling force, and the number of Si-H groups decreases over time, resulting in a decrease in the peeling force over time.
[0035] [(C) component] The component (C) of the present invention is an organopolysiloxane (excluding the above component (A)) having an average of one or more (meth)acrylic groups per molecule, and may be used alone or in combination of two or more. The weight average molecular weight of the component (C) is preferably 516 to 100,000, more preferably 516 to 30,000. Furthermore, the component (C) preferably does not have an aliphatic unsaturated bond. Here, the (meth)acrylic group means an acrylic group or a methacrylic group. Among them, those having an acrylic group are preferred.
[0036] Examples of organopolysiloxanes include cyclic siloxanes having structures represented by the following formulas (3) and (4), and organopolysiloxanes having a structure represented by the following formula (5). Those having a molecular weight or weight average molecular weight of 516 to 5,000 are preferred. Those having 3 to 10 siloxane units having a (meth)acrylic group are preferred, and those having no Si-H group or alkenyl group are preferred. As the (C) component, those having a (meth)acrylic group in the side chain of the organopolysiloxane are preferred, and among these, cyclic siloxanes having a (meth)acrylic group are more preferred. In the following formulas (3) to (5), R can be exemplified as the same as R in the above formula (1), and among these, an alkyl group having 1 to 8 carbon atoms is preferred.
[0037] D Ac q (3) [In the formula, D Ac AcRSiO 2 / 2 (Each R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and no aliphatic unsaturated bonds; Ac is CH2=CR 3 COOR 4 (R 3 is a hydrogen atom, or an alkyl or aryl group having 1 to 20 carbon atoms; R 4 is an alkyl group having 1 to 6 carbon atoms, which may have a branched or cyclic structure, and may contain an epoxy group, an ester bond, a urethane bond, an ether bond, an isocyanate bond, or a hydroxyl group. )) and q is 3 to 10.
[0038] D Ac r Ds (4) [D Ac is the same as above, and D is R 2 SiO 2 / 2 (Each R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and no aliphatic unsaturated bonds), r is a number from 3 to 10, and s is a number from 1 to 10.)
[0039] M Ac t M u DAc v D w T Ac x T y Q z (5) [Wherein, M is RSiO 1 / 2 , D is RSiO 2 / 2 , T is RSiO 3 / 2 , Q is SiO 4 / 2 (Each R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and no aliphatic unsaturated bonds), M Ac AcR2SiO 1 / 2 , D Ac AcRSiO 2 / 2 , T Ac AcSiO 3 / 2 Ac is CH2=CR 3 COOR 4 (R 3 is a hydrogen atom, or an alkyl or aryl group having 1 to 20 carbon atoms; R 4 is an alkyl group having 1 to 6 carbon atoms, which may have a branched or cyclic structure and may contain an epoxy group, an ester bond, a urethane bond, an ether bond, an isocyanate bond, or a hydroxyl group; t is an integer of 0 to 4, u is an integer of 0 to 7, and when u is 0, t is an integer of 2 to 4, and when u is 1, t is an integer of 1 to 4. v is an integer of 3 to 50, w is an integer of 3 to 200, x and y are both integers of 0 to 10, and z is 0 or 1. ]
[0040] In formula (5), t is an integer of 0 to 4, and u is an integer of 0 to 7. When u is 0, t is an integer of 2 to 4, and when u is 1, t is an integer of 1 to 4. u is preferably 2 or 3, in which case t is preferably 0. w is an integer of 3 to 200, preferably an integer of 5 to 180, and more preferably an integer of 10 to 160. v is an integer of 3 to 50, preferably an integer of 3 to 40, and more preferably an integer of 5 to 30. When v is less than 3, the curability may decrease if the amount of catalyst is reduced. Also, when v exceeds 50, the curability may decrease. Each of x and y is an integer of 0 to 8, preferably an integer of 0 to 6, and more preferably an integer of 0 to 3. When y exceeds 8, the curability may decrease, although the reason is not clear. z is 0 or 1. If z exceeds 1, the viscosity becomes too high and the peeling force becomes large, which is not preferable.
[0041] Specific examples of organopolysiloxane compounds having three or more (meth)acrylic groups and a molecular weight of 1,000 or more include the following. M2D5D Ac 3. M2D 20 D Ac 5. M Vi 2D 20 D Ac 5. M2D 30 D Ac 7. M φ 2D 2 30 D Ac 7. M2D 25 D Ac 7. M2D 65 D Ac 15 , M2D 2 65 D Ac 15 , M2D 61 D Ac 15 , M1M Ac 1D 10 D Ac 3. M3D 20 D Ac 5T1, M3D 110 D Ac 6T1, M2D 170 D Ac 22 , M2D 170 D Ac 20 Q1 In the above formula, M φ (Ph)R2SiO 1 / 2and (Ph) means a phenyl group.
[0042] The amount of component (C) is 0.01 to 10 parts by mass, and preferably 0.1 to 5 parts by mass, per 100 parts by mass of component (A). If it is less than 0.01 part by mass, the cure acceleration effect is not clear, while if it exceeds 10 parts by mass, the amount of migrating components increases, and a decrease in the residual adhesion rate and deterioration of adhesion may be observed.
[0043] The manufacturing method of component (C) is M2, M2D3, D Ac It can be obtained by blending raw materials such as D4, D5, etc., equilibrating them with an acid or alkali catalyst, and drying them under reduced pressure. In this case, it is preferable to blend an antioxidant. It is also preferable to use a strong acid such as trifluoromethanesulfonic acid as a catalyst.
[0044] The molecular weight or weight average molecular weight of component (C) is measured by Si-NMR. For Si-NMR, Win Lambda manufactured by JEOL Ltd. can be used as the device. The measurement method is to put 1.5 g of sample and 3.5 g of d-chloroform into a Teflon (registered trademark) sample tube with a diameter of 10 mm, stir well, set it in the Si-NMR, and measure with an accumulation number of 600 times. In the present invention, the organopolysiloxane having a structure represented by structural formula (5) of (C-2) is the weight average molecular weight, and the others are molecular weights.
[0045] [(D) component] The component (D) of the present invention is a compatibilizer that enables the component (C) to dissolve in the components (A) and (B), and is a straight-chain olefin having a melting point of 20° C. or less and a flash point of 40° C. or more. Specific examples include 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, decane, undecane, dodecane, tridecane, tetradecane, pentadecane, and hexadecane. Among these, straight-chain olefins having one or more unsaturated functional groups at the molecular terminals are preferred. Among these, preferred are straight-chain olefins having a vinyl value (the number of moles of unsaturated functional groups contained in 100 g) of 0.30 to 0.58 mol / 100 g, a melting point of 20° C. or lower, a flash point of 70° C. or higher, and one or more unsaturated functional groups at the molecular terminal, such as 1-octadecene, 1-hexadecene, and 1-tetradecene.
[0046] The melting point is measured by increasing the temperature from -150°C to 100°C at a rate of 10°C / min using a differential scanning calorimeter (e.g., DSC-3 manufactured by METTLER TOREDO). The flash point is measured by first measuring the flash point at -20°C to 300°C using the Seta closed cup flash point measurement method described in JIS K 2265-2. Next, for those that have a flash point of 79°C or higher measured using the Seta closed cup flash point measurement method, the flash point is measured from 10°C to 250°C using the Cleveland open cup flash point measurement method described in JIS K 2265.
[0047] By blending a certain amount of component (D), it is possible to make the acrylic group-containing organopolysiloxane, which is component (C), compatible with components (A) and (B), and it is expected that the acrylic group-containing organopolysiloxane will coordinate with the platinum catalyst without settling, and the catalytic activity will be improved, so that the curing reaction will proceed even with a small amount of platinum group metal catalyst. In addition, while other compounds with a compatibility effect often have a reduced curability even if they can be made compatible, the curability of the component (D) of the present invention does not decrease. Although the mechanism is unknown, it is thought that the curing is promoted by the amount of heat generated by the reaction of the unsaturated functional group and the SiH group. On the other hand, if the vinyl value exceeds 0.58 mol / 100 g, the H / Vi amount in the composition may be less than 1, and the curability may deteriorate.
[0048] If the melting point exceeds 20°C, the composition will become cloudy or solidify if it falls below the melting point of the blended component (D). At this point, it will no longer be effective as a compatibilizer, and component (C) will separate and settle over time. The flash point is 40°C or higher. This is because the flash point of the blended component (D) and the flash point of the entire composition will be the same value, so if the flash point of component (D) is below 40°C, the composition will be classified as a Class 4, Class 1 petroleum hazardous material.
[0049] [(E) component] The platinum group metal catalyst (E) of the present invention can be known as an addition reaction catalyst.Such platinum group metal catalyst can be, for example, platinum, palladium, rhodium, ruthenium, etc., and among these, platinum catalyst is particularly preferably used.This platinum catalyst can be, for example, platinum compound, platinum and vinylsiloxane complex, chloroplatinic acid alcohol solution or aldehyde solution, chloroplatinic acid and various olefin complex salts, chloroplatinic acid and vinylsiloxane complex, etc.
[0050] Conventionally, the concentration of the platinum group metal added to organopolysiloxane compositions for release papers or films to produce a cured coating has been 1 to 50 ppm, preferably 5 to 30 ppm, and more preferably 10 to 25 ppm, calculated as the mass of the platinum group metal relative to the total of components (A), (B), (C), and (D).
[0051] [Component (F)] The (F) addition reaction inhibitor of the present invention is a component that is added as necessary, and controls the catalytic activity of platinum group metal catalysts, and includes various organic nitrogen compounds, organic phosphorus compounds, acetylene compounds, oxime compounds, organic chloro compounds, etc. Specific examples include acetylene alcohols such as 1-ethynyl-1-cyclohexanol, 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-pentyn-3-ol, and 2-phenyl-3-butyn-2-ol, acetylene compounds such as 3-methyl-3-penten-1-yne and 3,5-dimethyl-3-hexen-1-yne, reaction products of acetylene compounds such as 1,1-dimethylpropynyloxytrimethylsilane with alkoxysilanes, siloxanes, or hydrogensilanes, vinylsiloxanes such as tetramethylvinylsiloxane cyclics, benzotriazole, diallyl Ma Examples include leate.
[0052] The amount of the component (F), when blended, is preferably 0.01 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the component (A).
[0053] [Metal components] The amount of metals other than platinum group metals in the organopolysiloxane composition of the present invention is 100 ppm (mass) or less, preferably 50 ppm or less, more preferably 10 ppm or less, and even more preferably 5 ppm or less. The metal component does not include the platinum group metal of component (E). Examples of the metal component include sodium, potassium, calcium, magnesium, iron, aluminum, copper, tin, barium, phosphorus, zinc, etc. The amount of metal is quantified using an ICP emission spectrometer using a sample obtained by adding sulfuric acid to 2 g of the composition and heating the composition to 900 ° C. in an electric furnace to incinerate the composition. If the amount of metal exceeds 100 ppm, there is a risk that the curing reaction will not proceed with a small amount of platinum group metal catalyst. In order to keep the amount of metal in the composition to 100 ppm or less, it is preferable to adsorb and remove each raw material used in the composition with a filter plate, activated carbon, silica, clay, bentonite, etc.
[0054] [Manufacturing method and optional ingredients] The organopolysiloxane composition of the present invention can be obtained by mixing the above-mentioned components (A) to (E) and, if necessary, the component (F) in predetermined amounts. The organopolysiloxane composition of the present invention can contain components that are usually added to organopolysiloxane compositions for release papers or release films, provided that the effects of the present invention are not impaired.
[0055] Examples of optional added components include high molecular weight linear organopolysiloxanes for the purpose of imparting slipperiness, silicone resins having aryl groups for the purpose of adjusting the release force, silicone resins, silica, and low molecular weight organopolysiloxanes having neither hydrogen atoms bonded to silicon atoms nor alkenyl groups.
[0056] The organopolysiloxane composition of the present invention has a kinematic viscosity of 500 mm at 25°C. 2 / s or less is preferable, and 10 to 450 mm 2 / s is more preferable, 50 to 430 mm 2 / s is even more preferable. If the kinetic viscosity is too low, the coating amount may be small, and if it is too high, the coating amount may vary and a large amount of mist may be generated. The kinetic viscosity is calculated from the specific gravity after measuring the absolute viscosity using the same EMS method as above.
[0057] [Applications / How to use] The organopolysiloxane composition of the present invention is applied to a sheet-like substrate such as paper or plastic film by a coating roll or the like, and then heat-cured by a conventional method. In this way, a silicone cured coating of the organopolysiloxane composition of the present invention is formed on one side of the sheet-like substrate, and is suitably used as a release sheet for release paper or release film. Examples of the paper substrate include glassine paper, polyethylene laminated paper, polyvinyl alcohol resin-coated paper, clay-coated paper, etc. Examples of the plastic film substrate include films of polyesters such as polyethylene, polypropylene, and polyethylene terephthalate.
[0058] The amount of the organopolysiloxane composition applied may be an amount sufficient to form a silicone cured film on the surface of the sheet-like substrate, and may be, for example, 0.1 to 5.0 g / m 2 Coating an excessively large amount of the coating may result in a decrease in the peeling performance. The temperature during heat curing varies depending on the type of substrate and the amount of coating, but is generally 60 to 200°C, preferably 100 to 190°C, and more preferably 120 to 180°C. 1 ~ 30 A cured coating can be formed on the substrate by heating for 1 to 60 seconds, more preferably 2 to 40 seconds. EXAMPLES
[0059] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The molecular weight of the component (C) listed below was determined by Si-NMR, and the kinetic viscosity was measured at 25°C using an EMS viscometer (EMS-1000S, Kyoto Electronics Industries Co., Ltd.) with a spherical probe of φ2 mm at a speed of 1,000 rpm for 10 seconds. The kinetic viscosity was calculated by dividing the obtained absolute viscosity value (mPa s) by the specific gravity of 0.98. It should be noted that Example 4 is a reference example.
[0060] [Raw materials used] Component (A) Methylvinylpolysiloxane (1) [Synthesis example] KOH (300 ppm) was added to 1 mole of 1,3-divinyltetramethyldisiloxane and 38.75 moles of octamethyltetrasiloxane, and polymerization was carried out at 150° C. for 6 hours, after which ethylene chlorohydrin was added in an amount 1.5 times the amount of KOH and neutralized at 150° C. for 3 hours. After concentration under reduced pressure at 120° C. and 20 mmHg for 3 hours, 5% activated carbon Shirasagi A (Osaka Gas Chemicals Co., Ltd.) was added, stirred for 2 hours, and then filtered using a filter plate NA500 (Advantec Co., Ltd.). The following structural formula {(CH2=CH)(CH3)2SiO 1 / 2}2{(CH3)2SiO} 155 Both ends of the molecular chain are blocked with dimethylvinylsiloxy groups, and all units other than the two ends are (CH3)2SiO units. The vinyl value is 0.0166 mol / 100 g, and the dynamic viscosity is 440 mm 2 Polysiloxane of 1 / s was obtained.
[0061] Methylvinylpolysiloxane (2) The composition was the same as that of the above methylvinylsiloxane (1), but after vacuum concentration, no activated carbon was added and filtration was carried out using filter paper No. 5A (manufactured by ADVANTEC).
[0062] (B) Component Methylhydrogenpolysiloxane Both ends of the molecular chain are blocked with trimethylsiloxy groups, and all units except for the ends are (CH3)HSiO units. The Si-H group content is 1.54 mol / 100 g, and the kinetic viscosity is 32 mm 2 / s Methyl hydrogen polysiloxane
[0063] (C) Component ·M2D 170 D Ac1 22 :Molecular weight 16,526 (M in the chemical formula is RSiO 1 / 2 , D is RSiO 2 / 2 (R is a methyl group), D Ac1 is (CH2=CHCOOCH2CH2CH2)(CH3)SiO 2 / 2 ·M2D 64 D Ac1 15 :Molecular weight 7,478 D Ac1 4:[(CH2=CHCOOCH2CH2CH2)(CH3)SiO 2 / 2 ]4 :Molecular weight 688
[0064] (D) Component 1-Octadecene: Vinyl value 0.396 mol / 100 g, melting point: 18°C, flash point 159°C 1-Tetradecene: Vinyl value 0.509 mol / 100 g, melting point: 13°C, flash point 113°C
[0065] (E) Component Platinum group metal catalysts: Complexes of platinum with vinylsiloxanes. Ingredient (F) 1-Ethynyl-1-cyclohexanol
[0066] Comparative component of (D) ·KF-96-50CS (viscosity 50mm 2 / s linear dimethylpolysiloxane) Vinyl value: 0 mol / 100 g, melting point: -50°C or less, flash point: 250°C or more 1-Octene: Vinyl value 0.89 mol / 100 g, Melting point: -102°C, Flash point: 8°C 1-Nonene: Vinyl value 0.792 mol / 100 g, melting point: -81°C, flash point 26°C 1-Heptene: Vinyl value 1.02 mol / 100 g, Melting point: -119°C, Flash point: -9°C 1-Eicosene: Vinyl value 0.355 mol / 100 g, Melting point: 26-30°C, Flash point: 151°C
[0067] [Example 1] 100 parts by mass of methylvinylpolysiloxane (1) as component (A), 2.2 parts by mass of methylhydrogenpolysiloxane as component (B), and M2D as component (C). 170 D Ac1 22 3.0 parts by mass of the activated carbon-treated product (activated carbon Shirasagi AS (manufactured by Osaka Gas Chemicals Co., Ltd.) was added at 1% by mass based on the total amount of siloxane, stirred for 2 hours, and then filtered through a filter plate NA500), 1.5 parts by mass of 1-octadecene as component (D), and 0.2 parts by mass of 1-ethynyl-1-cyclohexanol as component (F) were added and stirred until uniform, and then a platinum and vinyl siloxane complex was added as component (E) so that the platinum atomic mass equivalent was 20 ppm based on the total mass of components (A), (B), (C), and (D), and the mixture was stirred until uniform. The kinetic viscosity was 399 mm 2 A composition was prepared with a Si / s ratio and H / Vi ratio (ratio of Si-H groups in the composition to alkenyl groups in the composition) of 1.5. The amounts of metals other than platinum group metals contained in the composition were 0.7 ppm sodium and 1.1 ppm potassium (total 1.8 ppm).
[0068] [Example 2] A kinematic viscosity of 398 mm was obtained in the same manner as in Example 1, except that the amount of component (C) was changed to 2.0 parts by mass. 2 A composition having a pH of 1.5 / s and H / Vi of 1.5 was prepared. The amounts of metals other than platinum contained in the composition were 0.4 ppm sodium and 1.1 ppm potassium (total 1.5 ppm).
[0069] [Example 3] (C) Components are M2D 64 D Ac1 15The same composition as in Example 1 was used except that the activated carbon-treated product was used in the same manner, and the kinetic viscosity was 386 mm 2 A composition having a viscosity of 1.5 / s and H / Vi=1.5 was prepared. The amounts of metals other than platinum contained in the composition were 0.5 ppm sodium and 0.8 ppm potassium (total 1.3 ppm).
[0070] [Example 4] (C) Ingredient D Ac1 4 Filter plate NA500 processed product 2.0 mass parts were used, but in the same manner as in Example 1, a kinetic viscosity of 382 mm 2 A composition having a viscosity of 1.5 / s and H / Vi=1.5 was prepared. The amounts of metals other than platinum contained in the composition were 15 ppm sodium and 21 ppm potassium (total 36 ppm).
[0071] [Example 5] The component (A) is 100 parts by mass of methylvinylpolysiloxane (1), the component (B) is 4.7 parts by mass of methylhydrogenpolysiloxane, and the component (C) is M2D 170 D Ac1 22 0.5 parts by mass of the activated carbon treated product, 8 parts by mass of 1-octadecene as component (D), and 0.2 parts by mass of 1-ethynyl-1-cyclohexanol as component (F) were added and stirred until homogenous. Then, a platinum-vinylsiloxane complex was added as component (E) so that the platinum atomic mass equivalent was 20 ppm relative to the total mass of components (A), (B), (C), and (D), and the mixture was stirred until homogenous. The kinetic viscosity was 306 mm 2 A composition having a pH of 1.5 / s and H / Vi of 1.5 was prepared. The amounts of metals other than platinum contained in the composition were 0.4 ppm sodium and 0.7 ppm potassium (total: 1.1 ppm).
[0072] [Example 6] The same method as in Example 2 was used except that the amount of component (D) was 1.2 parts by mass of 1-tetradecene. The kinetic viscosity was 392 mm 2 A composition having a viscosity of 1.5 / s and H / Vi=1.5 was prepared. The amounts of metals other than platinum contained in the composition were 0.5 ppm sodium and 0.9 ppm potassium (total 1.4 ppm).
[0073] [Reference example] 100 parts by mass of methylvinylpolysiloxane (1) as component (A), 2.2 parts by mass of methylhydrogenpolysiloxane as component (B), and 0.2 parts by mass of 1-ethynyl-1-cyclohexanol as component (F) were added and stirred until uniform, after which a platinum and vinylsiloxane complex as component (E) was added in an amount equivalent to 100 ppm of platinum atomic mass relative to the combined mass of components (A) and (B), and the mixture was stirred until uniform. The resulting mixture had a kinetic viscosity of 418 mm 2 A composition was prepared with a Si / s ratio and H / Vi ratio (the ratio of Si-H groups in the composition to the alkenyl groups in the composition) of 2.0. The amounts of metals other than platinum contained in the composition were 0.3 ppm sodium and 0.7 ppm potassium (total 1.0 ppm).
[0074] [Comparative Example 1] 100 parts by mass of methylvinylpolysiloxane (1) as component (A), 2.2 parts by mass of methylhydrogenpolysiloxane (2) as component (B), and 0.2 parts by mass of 1-ethynyl-1-cyclohexanol as component (F) were added and stirred until uniform, and then a platinum and vinylsiloxane complex as component (E) was added in an amount equivalent to 20 ppm by platinum atomic mass relative to the total mass of components (A) and (B), and the mixture was stirred until uniform. 2 A composition having a pH of 1.0 / s and H / Vi of 2.0 was prepared. The amounts of metals other than platinum contained in the composition were 0.4 ppm sodium and 0.6 ppm potassium (total 1.0 ppm).
[0075] [Comparative Example 2] (C) M2D as component 170 D Ac1 22 The same composition as in Comparative Example 1 except that 2.0 parts by mass of 1.0 sucrose was added. The kinetic viscosity was 409 mm 2 A silicone release agent composition having a viscosity of 1.0 ppm / s and H / Vi=2.0 was prepared. The amounts of metals other than platinum contained in the composition were 0.5 ppm sodium and 0.9 ppm potassium (total 1.4 ppm).
[0076] [Comparative Example 3] The composition was the same as in Comparative Example 1, except that 1.5 parts by mass of 1-octadecene was added as component (D). 2 A silicone release agent composition having a viscosity of 1.5 / s and H / Vi=1.5 was prepared. The amounts of metals other than platinum contained in the composition were 0.4 ppm sodium and 0.7 ppm potassium (total 1.1 ppm).
[0077] [Comparative Example 4] As a comparison component for (D), KF-96-50CS (viscosity 50 mm 2 The composition was the same as in Comparative Example 2, except that 1.5 parts by mass of linear dimethylpolysiloxane (1.0 parts by mass / s) was added. 2 A silicone release agent composition having a viscosity of 1.0 ppm / s and H / Vi=2.0 was prepared. The amounts of metals other than platinum contained in the composition were 0.5 ppm sodium and 0.8 ppm potassium (total 1.3 ppm).
[0078] [Comparative Example 5] The composition was the same as in Comparative Example 2, except that 1.5 parts by mass of 1-octene was added as a comparative component (D). 2 A silicone release agent composition having a viscosity of 1.0 μm / s and H / Vi=1.03 was prepared. The amount of metal contained in the composition was 1.4 ppm, and the amounts of metals other than platinum contained in the composition were sodium 0.5 ppm and potassium 0.9 ppm (total 1.4 ppm).
[0079] [Comparative Example 6] The composition was the same as in Comparative Example 2, except that 1.5 parts by mass of 1-nonene was added as a comparative component (D). 2 A silicone release agent composition having a viscosity of 1.0 μm / s and H / Vi=1.08 was prepared. The amounts of metals other than platinum contained in the composition were 0.6 ppm sodium and 0.8 ppm potassium (total 1.4 ppm).
[0080] [Comparative Example 7] The composition was the same as in Comparative Example 2, except that 1.5 parts by mass of 1-heptene was added as a comparative component (D). 2A silicone release agent composition having a viscosity of 1.25 ppm and a viscosity of 1.24 was prepared. The amounts of metals other than platinum contained in the composition were 0.5 ppm sodium and 0.9 ppm potassium (total 1.4 ppm).
[0081] [Comparative Example 8] The composition was the same as in Comparative Example 2, except that 1.5 parts by mass of 1-eicosene was added as a comparative component (D). 2 A silicone release agent composition having a viscosity of 1.5 ppm / s and H / Vi=1.55 was prepared. The amounts of metals other than platinum contained in the composition were 0.5 ppm sodium and 0.8 ppm potassium (total 1.3 ppm).
[0082] [Comparative Example 9] As a comparative component (A), a kinetic viscosity of 398 mm was obtained by the same formulation as in Example 2, except that 100 parts by mass of methylvinylpolysiloxane (2) was used instead of 100 parts by mass of methylvinylpolysiloxane (1). 2 A silicone release agent composition having a viscosity of 1.5 / s and H / Vi=1.5 was prepared. The amounts of metals other than platinum contained in the composition were 37 ppm sodium and 65 ppm potassium (total 102 ppm).
[0083] The organopolysiloxane compositions obtained in the above examples were subjected to the following evaluations, and the results are shown in the table below. [Peeling Force] The organopolysiloxane composition was applied onto the metal roll of an offset transfer machine (manufactured by IHI Machine Systems Co., Ltd.), and the metal roll was brought into contact with the rubber roll and rotated for 45 seconds to uniformly spread. The composition was then transferred from the rubber roll to glassine paper ASP (manufactured by Ahlstrom-Munksjo). The glassine paper to which the composition had been transferred was heated in a hot air dryer at 120°C for 30 seconds to a thickness of 0.9 to 1.1 g / m. 2 After aging for 24 hours at 25°C in this state, TESA-7475 adhesive tape (tesa UK Ltd) was attached to the surface of the cured coating of this release paper (the surface transferred from the rubber roll) and cut into a size of 2.5cm x 18cm to prepare a test piece. This was sandwiched between glass plates and subjected to a pressure of 70gf / cm at 25°C.2 20gf / cm under load and at 70℃ 2 The test piece was aged for 24 hours under a load of 0.3 N / mm. After aging, one end of the test piece was peeled off, and the end of the adhesive tape was pulled at an angle of 180 degrees to the glassine paper at a peeling speed of 0.3 m / min. The force required to peel the tape (i.e., "peeling force") (N / 25 mm) was measured using a tensile tester (Shimadzu Corporation, AGS-50G type).
[0084] [Residual adhesion rate] The TESA-7475 adhesive tape after the peel strength measurement was attached to a stainless steel plate, and a 2 kg roller was moved back and forth once to apply a load. After leaving it for 30 minutes, one end of the TESA-7475 adhesive tape was peeled off and the end was Stainless steel plate The tape was pulled in a direction at an angle of 180 degrees to the tape. The force required to peel the tape at a peeling speed of 0.3 m / min (hereinafter referred to as "peeling force A", N / 25 mm) was measured. As a blank, Stainless steel plate A 2 kg roller was rolled back and forth once to apply a load to the surface. After leaving the surface for 30 minutes, one end of the TESA-7475 adhesive tape was peeled off and the end was Stainless steel plate The tape was pulled in a direction at an angle of 180 degrees to the tape. The force required to peel the tape off at a peeling speed of 0.3 m / min (hereinafter referred to as "peeling force B", N / 25 mm) was measured. The residual adhesion rate (%) was calculated by (value of peel force A) / (value of peel force B)×100.
[0085] [Curability] In the same manner as for the peeling force, each organopolysiloxane composition was transferred to a glassine paper ASP using an offset transfer machine. The glassine paper to which the organopolysiloxane composition had been transferred was heated in a hot air dryer at 120°C for 30 seconds to give a thickness of 0.9 to 1.1 g / m 2 The release paper was removed from the dryer and the cured coating surface was immediately rubbed strongly with an index finger 10 times, and then red magic marker was applied to observe the ink thickness and the condition of the cured coating. The results were evaluated based on the following criteria: If there are almost no visible finger marks, select "○". If the fingerprints are faint, mark them as "△". If the fingerprints are dark, mark them with "X".
[0086] [Amount of silicone transferred] In the same manner as in the case of peeling force measurement, a 38 μm thick polyester film was placed on the surface of the cured film of the organopolysiloxane composition formed on the surface of glassine paper, and after 20 hours of pressure bonding at room temperature under a pressure of 0.98 MPa, the polyester film was removed from the cured film. An oil-based ink (trade name: Magic Ink, manufactured by Teranishi Chemical Industry Co., Ltd.) was applied to the surface of the polyester film that had been in contact with the cured film, and silicone migration was evaluated based on the degree of repelling. The results were evaluated based on the following criteria: No ink repellency (no or very little silicone migration) is marked as "○" If there is ink repellency (lots of silicone migration), it is marked as "X".
[0087] [Table 1]
[0088] [Table 2]
[0089] [Table 3]
[0090] [Table 4]
[0091] [Table 5]
[0092] In all of the Examples, by using the components (C) and (D) in combination, the appearance was colorless and transparent, and no separation or sedimentation occurred after leaving the coating liquid for 8 hours. In the production of release paper, it is said that the bath life of the coating liquid needs to be 8 hours or more, preferably 16 hours or more. Furthermore, all of the Examples showed values for peel strength, residual adhesion, curability, and silicone migration that were not significantly different from the Reference Example (an example in which catalyst (E) was added in an amount of 100 ppm platinum relative to the total amount of components (A) and (B) and then sufficiently cured). This shows that the silicone was sufficiently cured despite the small platinum amount of 20 ppm.
[0093] In addition, Comparative Example 1 has the same composition as the Reference Example but with the addition of 0.8 parts of catalyst (20 ppm platinum). However, compared to the Reference Example and Examples, it shows that the peel strength is higher, the residual adhesion rate is lower, the curing properties are poor, and the amount of silicone migration is also large, indicating insufficient curing. In Comparative Example 2, component (C) was added to the composition of Comparative Example 1, and thus good properties were obtained in terms of peel strength, residual adhesion rate, curability, and silicone migration amount. However, since component (D) was not added, the appearance of the coating liquid (immediately after mixing) was milky white, and after leaving it to stand for 8 hours, component (C) had settled and separated. Comparative Example 3 is a formulation in which component (C) is omitted from Example 1. The appearance is good, but the curability is poor, resulting in high peel strength, a low residual adhesion rate, and an increased amount of migration, resulting in ink repellency. Comparative Example 4 is a formulation in which component (D) was changed to KF-96-50CS. In this case, the peeling properties were slightly worsened and the appearance became cloudy. In Comparative Examples 5 to 7, the molecular weight of component (D) was low and the vinyl value was 0.58 mol / 100 g or more, resulting in a low H / Vi of 1.4 or less for the composition. Because H / Vi was too low, the curing properties were poor, resulting in a slightly high peel force, a slightly low residual adhesion rate, and poor curing properties and silicone migration properties. Comparative Example 8 is a formulation in which component (D) was replaced with 1-eicosene. 1-eicosene solidifies at room temperature, losing its effect as a compatibilizer and causing the coating liquid to become slightly cloudy in appearance. When this coating liquid was left to stand for 8 hours, component (C) had settled and separated. Comparative Example 9 has the same composition as Example 1, but the metal content in the composition is 100 ppm or more. In this case, the peel force is high, the residual adhesion rate is low, and the curing property is poor. From the above results, it is clear that the composition of the present invention does not become cloudy and sufficient silicone curing can be achieved with a small amount of platinum.
Claims
1. An addition reaction curable organopolysiloxane composition comprising the following components (A) to (E), in which the amount of metals other than platinum group metals in the composition is 100 ppm or less: (A) an organopolysiloxane having an average of two or more silicon-bonded alkenyl groups per molecule: 100 parts by mass, (B) an organohydrogenpolysiloxane having an average of two or more silicon-bonded hydrogen atoms (Si—H groups) per molecule: an amount in which the number of moles of Si—H groups corresponds to 1 to 5 times the number of moles of alkenyl groups in component (A); (C) Formula (5) below M Ac t M u D Ac v D w T Ac x T y Q z (5) [In the formula, M is R 3 SiO 1 / 2 ,D is R 2 SiO 2 / 2 , T is RSiO 3 / 2 , Q is SiO 4 / 2 (Each R is independently an unsubstituted or substituted monovalent hydrocarbon group having 1 to 12 carbon atoms and no aliphatic unsaturated bonds), M Ac AcR 2 SiO 1 / 2 , D Ac AcRSiO 2 / 2 , T Ac AcSiO 3 / 2 Ac is CH 2 =CR 3 COOR 4 (R 3 is a hydrogen atom, or an alkyl or aryl group having 1 to 20 carbon atoms; R 4 is an alkyl group having 1 to 6 carbon atoms, which may have a branched or cyclic structure, and may contain an epoxy group, an ester bond, a urethane bond, an ether bond, an isocyanate bond, or a hydroxyl group. t is an integer from 0 to 4, u is an integer from 0 to 7, and when u is 0, t is an integer from 2 to 4, and when u is 1, t is an integer from 1 to 4. v is an integer from 3 to 50, w is an integer from 5 to 200, x and y are both integers from 0 to 10, and z is 0 or 1. (excluding the above component (A)): 0.01 to 10 parts by mass of an organopolysiloxane having a (meth)acrylic group represented by the formula: (D) a linear olefin having a melting point of 20° C. or lower and a flash point of 40° C. or higher: 0.1 to 20 parts by mass, (E) Platinum group metal catalyst: 1 to 50 ppm by mass of platinum group metal based on the total of components (A), (B), (C) and (D).
2. 2. The addition reaction curable organopolysiloxane composition according to claim 1, further comprising (F) 0.01 to 5 parts by weight of an addition reaction inhibitor per 100 parts by weight of component (A).
3. 3. The addition reaction curable organopolysiloxane composition according to claim 1, wherein the weight average molecular weight of component (C) is 100,000 or less.
4. 4. The addition reaction curable organopolysiloxane composition according to claim 1, wherein component (C) is an organopolysiloxane having a (meth)acrylic group on the side chain of the organopolysiloxane.
5. 5. The addition reaction curable organopolysiloxane composition according to any one of claims 1 to 4, wherein component (C) is a cyclic siloxane having a (meth)acrylic group.
6. 6. The addition reaction curable organopolysiloxane composition according to any one of claims 1 to 5, wherein component (C) is an organopolysiloxane having three or more (meth)acrylic groups in one molecule.
7. 7. The addition reaction curable organopolysiloxane composition according to any one of claims 1 to 6, wherein component (D) is a straight-chain olefin having a vinyl value (the number of moles of unsaturated functional groups contained in 100 g) of 0.30 to 0.58 mol / 100 g, a melting point of 20°C or lower, a flash point of 70°C or higher, and one or more unsaturated functional groups at the molecular terminals.
8. The addition reaction curable organopolysiloxane composition according to any one of claims 1 to 7, which is for use in release paper or release film.
Citation Information
Patent Citations
JP1960-013709B
JP1972032072U
Radiationncurable silicone release composition
JP1979162787A
Silicone dissociable coating composition
JP2009513740A
Silicone composition for release paper or release film, release paper, and release film
JP2016053107A